1993
DOI: 10.1007/bf00941505
|View full text |Cite
|
Sign up to set email alerts
|

The children of divorce parenting intervention: Outcome evaluation of an empirically based program

Abstract: Examined efficacy of an empirically based intervention using 70 divorced mothers who participated in a 12-session program or a wait-list condition. The program targeted five putative mediators: quality of the mother-child relationship, discipline, negative divorce events, contact with fathers, and support from nonparental adults. Posttest comparisons showed higher quality mother-child relationships and discipline, fewer negative divorce events, and better mental health outcomes for program participants than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(52 citation statements)
references
References 59 publications
3
48
0
1
Order By: Relevance
“…In addition, how caregivers communicate with their children around stressful family events was assessed with the sixitem Talk with Reassurance subscale of the Caregiver Expression of Emotion Questionnaire, which was developed for this project (e.g., "Reassure child that you are dealing with your sadness," α = .74). These scales have been demonstrated to have adequate psychometric properties (Ayers et al, 1998;Jensen, Boyce, & Hartnett, 1983;Jones & Twohey, 1998;Schaefer, 1965;Wolchik et al, 1993).…”
Section: Caregiver-child Relationship Qualitymentioning
confidence: 95%
“…In addition, how caregivers communicate with their children around stressful family events was assessed with the sixitem Talk with Reassurance subscale of the Caregiver Expression of Emotion Questionnaire, which was developed for this project (e.g., "Reassure child that you are dealing with your sadness," α = .74). These scales have been demonstrated to have adequate psychometric properties (Ayers et al, 1998;Jensen, Boyce, & Hartnett, 1983;Jones & Twohey, 1998;Schaefer, 1965;Wolchik et al, 1993).…”
Section: Caregiver-child Relationship Qualitymentioning
confidence: 95%
“…models are necessary to tease out which of these effects are overlapping or unique. Prior studies have demonstrated that program-induced improvements in parenting (Martinez & Forgatch, 2001;Tein et al, 2004;Wolchik et al, 1993) mediate the effects of family-based prevention programs for children whose parents are divorced or separating. The current study tests a replication of the effects of improving parenting for a new population, bereaved children, and tests potential program mediation effects of several other child variables (e.g., coping, inhibition of emotional expression) and family variables (e.g., stressful events) that have not previously been tested in randomized experimental trials of prevention programs for children who experience stressful family disruptions.…”
Section: Implications Of Mediation For Intervention Development and Tmentioning
confidence: 98%
“…The NBP has shown high levels of efficacy in multiple randomized experimental trials, conducted in the context of a University-based research center (Wolchik et al 1993(Wolchik et al , 2002Dawson-McClure et al 2004). These trials have demonstrated impressive positive benefits of the program to prevent child mental health problems, substance use, precocious sexual behavior, and improve academic performance and self-esteem over 6 years later.…”
Section: Application Of Qfd To Redesign Of An Efficacious Prevention mentioning
confidence: 97%
“…The current paper describes the use of QFD to redesign a program (NBP) that was developed and tested in the science system (Sandler et al 2006;Weiss and Wolchik 1998;Wolchik et al 1993Wolchik et al , 2002 for delivery and evaluation in the prevention delivery system. In terms of the CDC framework it involves linking the research system with the support system (training and technical assistance) and the delivery system (actual implementation in community agencies).…”
Section: Introductionmentioning
confidence: 99%